Hubungan Iklim Keselamatan Kerja dengan Tindakan Tidak Aman pada Proyek Pembangunan Gedung X Semarang - Novia Larisca; Baju Widjasena; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Safety climate refers to organizational perceptions, policies, procedures and practices. Safety climate could affect the way workers carry out work in the form of safe and unsafe actions. Unsafe action was incompatibility between procedures or rules with the actions taken. The purpose of this study was to analyze the relationship of safety climate with unsafe actions on the building project X Semarang. Dependent variable in this study was unsafe action. While the independent variables were commitment and management competency in safety, management safety empowerment, and management safety justice that were dimensions from the safety climate. The study used a quantitative method with a cross sectional design. Samples were 87 people with the proportional sampling method. Instrument used Nordic Safety Climate Questioner and observation checklist for unsafe act. The results of observations show that unsafe actions outweigh safe actions. Based on the results of the Rank Spearman test, there was a relationship between management safety empowerment and management safety justice with unsafe actions.